2023
DOI: 10.3390/ijms24066007
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Histone Modifications in the Pathogenesis of Diabetic Kidney Disease

Abstract: Diabetic kidney disease (DKD) is the leading cause of chronic kidney disease. The pathogenesis of DKD is multifactorial, with several molecular pathways implicated. Recent data suggest that histone modification plays an important role in the development and progression of DKD. Histone modification appears to induce oxidative stress, inflammation and fibrosis in the diabetic kidney. In the present review, we summarize the current knowledge on the association between histone modification and DKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 118 publications
0
6
0
Order By: Relevance
“…Histone acetylation has also been linked to diabetic complications, such as diabetic retinopathy [138] (Figure 1). Recent evidence indicates that histone modification appears to initiate oxidative stress, inflammation, and fibrosis in the diabetic kidney [139]. Research conducted on diabetic mice showed that early glomerulosclerosis was linked to diminished H3K9 and H3K23 histone acetylation [140].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histone acetylation has also been linked to diabetic complications, such as diabetic retinopathy [138] (Figure 1). Recent evidence indicates that histone modification appears to initiate oxidative stress, inflammation, and fibrosis in the diabetic kidney [139]. Research conducted on diabetic mice showed that early glomerulosclerosis was linked to diminished H3K9 and H3K23 histone acetylation [140].…”
Section: Discussionmentioning
confidence: 99%
“…Since gluconeogenesis is a primary factor in hepatic glucose production in people with diabetes and insulin impacts gluconeogenesis through transcription, identifying the insulin signaling pathways that affect gluconeogenic gene transcription and gluconeogenesis can contribute to comprehending PTDM pathophysiology (Figure 1). inflammation, and fibrosis in the diabetic kidney [139]. Research conducted on diabetic mice showed that early glomerulosclerosis was linked to diminished H3K9 and H3K23 histone acetylation [140].…”
Section: Pathways Associated With Ptdmmentioning
confidence: 99%
“…The nature of these modifications can be either activating, repressive, or inheritable. In individuals with T2D, if the balance of histone modifications is altered, it leads to changes in gene expressions that can further contribute to the advancement of the disease [ 41 ]. One of the main histone modifications associated with T2D is histone acetylation, which is an activating modification linked to increased gene expression.…”
Section: Factors Leading To Development Of T2dmentioning
confidence: 99%
“…In the context of DKD, histone modifications are crucial in regulating gene expression patterns that contribute to the progression of the disease [306,307]. For instance, studies have shown that certain histone modifications, such as acetylation and methylation, are associated with the dysregulation of genes involved in inflammation [308][309][310][311], fibrosis [312,313], and oxidative stress responses [314,315] in DKD.…”
Section: Genetics and Epigenetics Of Dkdmentioning
confidence: 99%